Temporal Trends in and Factors Associated With Bleeding Complications Among Patients Undergoing Percutaneous Coronary Intervention: A Report From the National Cardiovascular Data CathPCI Registry - Subherwal, Sumeet (2012)
OBJECTIVES: The purpose of this study was to examine temporal trends in post-percutaneous coronary intervention (PCI) bleeding among patients with elective PCI, unstable angina (UA)/non–ST-segment elevation myocardial infarction (NSTEMI), and ST-segment elevation myocardial infarction (STEMI). BACKGROUND: The impact of bleeding avoidance strategies on post-PCI bleeding rates over time is unknown. METHODS: Using the CathPCI Registry, we examined temporal trends in post-PCI bleeding from 2005 to 2009 among patients with elective PCI (n = 599,524), UA/NSTEMI (n = 836,103), and STEMI (n = 267,632). We quantified the linear time trend in bleeding using 3 sequential logistic regression models: 1) clinical factors; 2) clinical + vascular access strategies (femoral vs. radial, use of closure devices); and 3) clinical, vascular strategies + antithrombotic treatments (anticoagulant ± glycoprotein IIb/IIIa inhibitor [GPI]). Changes in the odds ratio for time trend in bleeding were compared using bootstrapping and converted to risk ratio. RESULTS: An approximate 20% reduction in post-PCI bleeding was seen (elective PCI: 1.4% to 1.1%; UA/NSTEMI: 2.3% to 1.8; STEMI: 4.9% to 4.5%). Radial approach remained low (<3%), and closure device use increased marginally from 44% to 49%. Bivalirudin use increased (17% to 30%), whereas any heparin + GPI decreased (41% to 28%). There was a significant 6% to 8% per year reduction in annual bleeding risk in UA/NSTEMI and elective PCI, but not in STEMI. Antithrombotic strategies were associated with roughly half of the reduction in annual bleeding risk: change in risk ratio from 7.5% to 4% for elective PCI, and 5.7% to 2.8% for UA/NSTEMI (both p <0.001). CONCLUSIONS: The nearly 20% reduction in post-PCI bleeding over time was largely due to temporal changes in antithrombotic strategies. Further reductions in bleeding complications may be possible as bleeding avoidance strategies evolve, especially in STEMI.